Haatzaai Artikelen: Pasal Karet dalam Hukum Kolonial di Hindia Belanda - Nadia Nuraini Hasni; Faizal Arifin; Ella Nurlailasari (UIN Sunan Gunung Djati Bandung, 2021)
The Dutch Colonial Government formed a colonial legal system aimed at strengthening power in the Dutch East Indies. Haatzaai Artikelen is one of the products of colonial law used to sanction anyone who criticizes Dutch rule. The study of Haatzaai Artikelen is interesting because colonial legal instruments impose injustice through criminal offense with accusations of utterance or expressions of hostility, hatred, and contempt for Dutch political interests. This Research uses the historical method with this legal approach aims to analyze the implementation of Haatzaai Artikelen and its impact on the struggle against colonialism. The results showed that the Dutch colonial government interpreted Haatzaai Artikelen according to their political interests. Also, the Dutch Colonial Government and its judicial system systematically used the Haatzaai Artikelen as a rubber article to arrest Indonesian activists, silence, and imprison them. The implementation and demands of the Haatzaai Artikelen offense have implications for the rise of resistance against Dutch colonialism and exploitation, and on the other hand, have weakened the struggles of several figures so that the application of this punishment affects the dynamics of the Indonesian national movement. Keywords: Haatzaai Artikelen, Colonialism, Netherlands Indies’ Laws, History of Law, Hate Speech.